A Study of the relationship between leadership styles (transformational and transactional) and employees’ job satisfaction in the electronic industries, in Penang. - Chan, Fung Lan (2009)
Kajian ini adalah untuk memeriksa hubungan antara kepimpinan (transformasi dan transaksi) dan kepuasan bekerja dalam industri elektronik.